Leiomiomatose peritoneal disseminada: uma condição rara - Vilela,Fernanda (2017)
Leiomyomatosis peritonealis disseminata (LPD) is a rare disease primarily found in young women. LPD has a genetic and hormonal component. Normally the diagnosis is established during an abdominal surgery because most of the affected women are asymptomatic. There aren't guidelines for LPD treatment, but it can involve surgery or hormonal therapy. The authors describe the case of a young asymptomatic pregnant woman who was diagnosed with LPD during cesarean. As it is a rare condition, it is important to report clinical cases with different experiences to alert the medical community to this patology